Identifying marine phytoplankton - Tomas, Carmelo R.; Hasle, Grethe R. (Grethe Rytter), 1920- (Academic Press, 1997)
Identifying Marine Phytoplankton is an accurate and authoritative guide to the identification of marine diatoms and dinoflagellates, meant to be used with tools as simple as a light microscope. The book compiles the latest taxonomic names, an extensive bibliography (referencing historical as well as up-to-date literature), synthesis and criteria in one indispensable source. Techniques for preparing samples and containing are included as well as hundreds of detailed, helpful information. Identifying Marine Phytoplankton is a combined paperback edition made available by popular demand of two influential books published earlier--Marine Phytoplankton and Identifying Marine Diatoms and Dinoflagellates. Key Features * Contains hundreds of illustrations showing critical characteristics necessary for proper identification, plus keys and other guides * Provides up-to-date taxonomic revisions * Includes species from around the world * Updates synthesis of modern and historical literature presented by active researchers in the field * Compiles literature from around the world into one handy source.